ICT Initiatives in India to Combat COVID-19 - Nirupam Bajpai; John Biberman; Manisha Wadhwa (Columbia University, Earth Institute, Center for Sustainable Development (CSD), 2020)
The great loss of life and economic damage COVID-19 has wrought across the world has not left India untouched. In these tough times, Information and Communications Technology (ICT) has emerged as a key means of both resolving challenges caused by the pandemic and responding to the new reality of the everyday. Government at the central and state levels has actively engaged with the private sector to develop ICT solutions, particularly identification, isolation, contact tracing, and treatment, to deal with the evolving situation in the country. Of particular benefit have been the growing number of mobile applications and Artificial Intelligence (AI) based tools which have emerged during this time. However, the use of ICT involves its own set of challenges, especially concerning privacy safeguards. Governments must ensure the use of ICT is fair and proportional not only during the times of pandemic, but also in the post-COVID-19 era. Countries like South Korea and Hong Kong illustrate emergent best practices for the use of ICT in such crises.
Keywords: 330